2016
DOI: 10.1016/j.taap.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of levonorgestrel and ethinylestradiol on brain aromatase ( cyp19a1b ) in zebrafish specific in vitro and in vivo bioassays

Abstract: Estrogens and progestins are widely used in combination in human medicine and both are present in aquatic environment. Despite the joint exposure of aquatic wildlife to estrogens and progestins, very little information is available on their combined effects. In the present study we investigated the effect of ethinylestradiol (EE2) and Levonorgestrel (LNG), alone and in mixtures, on the expression of the brain specific ER-regulated cyp19a1b gene. For that purpose, recently established zebrafish-derived tools we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Fertilized cyp19a1b -GFP transgenic zebrafish eggs were exposed to chemicals (alone or in mixtures) or to solvent control (DMSO, 0.02% v / v ) according to [ 12 ]. Each experimental condition contained 20 embryos in 100 mL of water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fertilized cyp19a1b -GFP transgenic zebrafish eggs were exposed to chemicals (alone or in mixtures) or to solvent control (DMSO, 0.02% v / v ) according to [ 12 ]. Each experimental condition contained 20 embryos in 100 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture experimental design was developed based on relative potency of single compounds according to [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, using wild-type and transgenic Tg(cyp19a1b)-GFP embryo zebrafish, we showed that some progestins are able to exert additive effects to the environmental estrogens, therefore acting as estrogenic-like compounds. This resulted in the activation of the estrogen-specific marker, the cyp19a1b aromatase gene, in the developing zebrafish brain through the activation of ERs [ 99 , 117 ]. Furthermore, we have studied the effects of cadmium (Cd, a heavy metal) exposure on estrogen signaling in zebrafish.…”
Section: A Zebrafish Model For Predicting the Estrogenicity And Camentioning
confidence: 99%